Parent's love and other islamic stories - Rumy, Ishrat J. (Goddword Delhi, 2003)
Parent's Love and Other Islamic Stories by Ishrat Rumy is a collection of heartwarming and inspiring narratives that reflect Islamic values and teachings. Each story beautifully illustrates themes of parental love, compassion, honesty, patience, and faith in Allah. The stories aim to nurture moral development in young readers while deepening their understanding of Islamic principles. Through relatable characters and real-life scenarios, the book emphasizes the importance of family bonds, kindness, and righteousness. It serves as both an engaging read and a valuable tool for instilling ethical behavior and spiritual growth in children and adults alike.